Enhancing Employee Commitment through Flexible Working Arrangements and Sustainable H.R. Practices in Indonesian Startups - Rina, Rina; Basalamah, Indira; Abdullah, Akmal (Universitas Mercu Buana, 2025)
Objectives: This study aims to evaluate the extent and kind of flexible work arrangements(FWAs) in Indonesian startups, considering alternatives for remote work, fluctuating work schedules, and other forms of flexibility. Additionally, it examines how employee commitment is affected by flexible work schedules. And explores the role of sustainable human resource practices in moderating the relationship between employee commitment and flexible work schedules.Methodology: This study employs a structural equation model (SEM) to analyze data collected from 247 employees, assessing the relationships among FWAs, sustainable HR practices, and employee commitment.Finding: This study confirms that FWAs positively contribute to employee commitment, with sustainable HR practices acting as a moderating factor. FWAs enhances job satisfaction and reduces stress, while sustainable HR strategies support employee engagement in the digital era. These findings highlight the importance of integrating FWAs and sustainable HR practices to create an adaptive work environment, improve retention, and drive productivity in the startup ecosystem.Conclusion: This study highlights the significance of FWAs in increasing employee commitment, particularly when supported by sustainable HR practices. By integrating FWAs with sustainability-driven HR strategies, startups can cultivate a resilient workforce, promote long-term retention, and drive innovation in dynamic and evolving business landscapes.